2019
DOI: 10.1016/j.dadm.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anxiety symptoms in persons with dementia: A systematic review

Abstract: Introduction Anxiety is a common symptom for those experiencing dementia and is associated with worse outcomes. The aim of the study was to examine which anxiety tools have been validated compared with a gold standard diagnostic criterion in persons with dementia. Methods We completed a systematic review of the literature, which was registered a priori with PROSPERO (CRD42016042123). Three databases were searched, MEDLINE, EMBASE, and PsycINFO, as well as the gray liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The increased prevalence of phobic changes in our FTD cohort is in line both with clinical experience and previous single-case studies ( Clark et al., 2014 ). This finding foregrounds a symptom that has been largely overlooked by standard instruments in the field ( Cummings et al., 1994 ; Goodarzi et al., 2019 ; Goyal, Bergh, Engedal, Kirkevold, & Kirkevold, 2017 ), while extending previous evidence that anxiety is a common symptom in dementia, especially FTD ( Porter et al., 2003 ). More specifically, development of new phobic reactivity appears to be a hallmark of FTD, at odds both with the direction of phobic alterations observed in the present AD group and with previous work indicating that phobic reactivity tends to become attenuated in healthy older people ( Byers et al., 2010 ; Chou et al., 2011 ; Grenier et al., 2019 ; Sigström et al., 2016 ; Stinson et al., 2007 ).…”
Section: Discussionsupporting
confidence: 78%
“…The increased prevalence of phobic changes in our FTD cohort is in line both with clinical experience and previous single-case studies ( Clark et al., 2014 ). This finding foregrounds a symptom that has been largely overlooked by standard instruments in the field ( Cummings et al., 1994 ; Goodarzi et al., 2019 ; Goyal, Bergh, Engedal, Kirkevold, & Kirkevold, 2017 ), while extending previous evidence that anxiety is a common symptom in dementia, especially FTD ( Porter et al., 2003 ). More specifically, development of new phobic reactivity appears to be a hallmark of FTD, at odds both with the direction of phobic alterations observed in the present AD group and with previous work indicating that phobic reactivity tends to become attenuated in healthy older people ( Byers et al., 2010 ; Chou et al., 2011 ; Grenier et al., 2019 ; Sigström et al., 2016 ; Stinson et al., 2007 ).…”
Section: Discussionsupporting
confidence: 78%
“…In a systematic review about the ways to evaluate anxiety symptoms in persons with dementia (Goodarzi et al, 2019 ), three validated tools were identified: the Geriatric Anxiety Inventory, Penn State Worry Questionnaire, and the Rating Anxiety in Dementia (RAID) scale. Goodarzi et al ( 2019 ) reported that the RAID has the highest sensitivity for anxiety and was specifically designed for those experiencing dementia; thus, it may be useful to take advantage of these scales. However, information about the impact of anxiety on capacity to consent to treatment in individuals with dementia is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty subjects were diagnosed with dementia and excluded, while the remaining 299 were diagnosed with normal cognition ( n = 117) or MCI ( n = 182) and were enrolled in the study. Subjects with dementia were excluded because of concerns they would not be able to reliably answer the study questionnaires since we did not use dementia‐specific tools 49,50 for the screening of anxiety and depression (see later). The study is part of a wider research project carried out at our geriatric unit and designed to collect data on different characteristics of outpatients.…”
Section: Methodsmentioning
confidence: 99%